1993
DOI: 10.1002/ptr.2650070711
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of antiinflammatory and antithermal burn action of CPase from Aloe arborescens Miller var. natalensis Berger in rats and mice

Abstract: Carboxypeptidase (CPase) was partially purified from Kidachi aloe (Aloe arborescens Miller var. natalensis Berger) by an FPLC system, and was administered intravenously to female ICR mice with inflammation. The enzyme preparation exhibited significant analgesic effects and inhibited vascular permeability in the abdominal region. It also revealed an antithermal burn action on the hind paw, when it was administered to female Wistar rats intravenously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The ammonium sulphate precipitated fraction of the A. vera gel also reported for in-vitro anti-bradykinin activity [31] and a 14 kDa radical scavenging glycoprotein had been reported for inhibiting cyclooxygenase-2 and thromboxane A2 synthase from A. vera gel [23]. Another study reported a carboxy-peptidase activity of the A. vera leaf gel, inactivates bradykinins and produces an antiinflammatory effect [32,33]. It has been reported earlier that aqueous extract from A. vera gel showed anti-inflammatory activity by inhibiting the action of arachidonic acid pathway via cyclooxygenase [34].…”
Section: Discussionmentioning
confidence: 92%
“…The ammonium sulphate precipitated fraction of the A. vera gel also reported for in-vitro anti-bradykinin activity [31] and a 14 kDa radical scavenging glycoprotein had been reported for inhibiting cyclooxygenase-2 and thromboxane A2 synthase from A. vera gel [23]. Another study reported a carboxy-peptidase activity of the A. vera leaf gel, inactivates bradykinins and produces an antiinflammatory effect [32,33]. It has been reported earlier that aqueous extract from A. vera gel showed anti-inflammatory activity by inhibiting the action of arachidonic acid pathway via cyclooxygenase [34].…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, it was observed that Aloe vera could modulate Salmonella OmpR mediated inflammation. It significantly reduced hyperalgesia which may be attributed to inhibition of prostaglandins production (Langmead et al, 2004) and due to the release of an enzyme known as carboxypeptidase which hydrolyses bradykinin (Obata et al, 1993;Shelton, 1991;Bautista-Perez et al, 2004) thus resulting in an analgesic effect. The results coincide well with those reported by Sarkar et al (2005).…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies indicated the presence of anthraquinone aloin, polysachharides, reducing sugars, organic acids, glycoproteins, sterols, terpenes, etc. in Aloe preparations [20,21].…”
Section: Spectral Analysismentioning
confidence: 99%